The Effect of Servant Leadership on Teacher Performance With Organizational Commitment as a Mediation Variable in High Schools - Fahmalatif, Farida (International Journal of Social and Management Studies, 2020)
The purpose of this study was to determine the effect of servant leadership on employee performance with organizational commitment as an intervening variable in high school. This study uses a Structural Equation Modeling (SEM) method to determine the effect of servant leadership on employee performance with organizational commitment as an intervening variable in high school. Data was collected by distributing questionnaires and the sampling method used was purposive sampling method. Testing research hypotheses using software smartPLS 3.2.7. The results of this study are that Servant leadership has a significant effect on teacher performance. Servant leadership has a positive and significant effect on organizational commitment. Organizational commitment has a positive and significant effect on employee performance. Organizational commitment has an effect as an intervening variable on the relationship between servant leadership and teacher performance